THE EFFECT OF INTERNAL CONTROL ON FRAUD PREVENTION BASED ON THE CAUSE FACTORS: Empirical Study on A Construction Company in Surabaya - Yahya, Fifi Arida; Venusita, Lintang (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2022)
The purpose of this study is to determine the effect of control environment, risk assessment, control activities, information and communication, and monitoring activities on fraud prevention based on the factors causing fraud adopted from the fraud pentagon theory, which consists of pressure, opportunity, rationalization, ability, and arrogance. The population in this study are employees of a construction service company in the city of Surabaya. The sampling technique used in this study is the non-probability sampling method, which means all members of the population are used as the sample in the study. The number of samples used in this study is 57 respondents, who were employees of the company. The data analysis method used in this study is the Structural Equation Modeling (SEM) based on its variant, namely Partial Least Square (PLS), using the smart pls software version 3.3.5. The results of this study indicate that the control environment, risk assessment, and monitoring activities have positive and significant effect on fraud prevention, but control and information & communication activities have no effect on fraud prevention.